Nano zinc oxide additive for the enhancement of lubricant properties - Hajam, Sanoj; Trital, Hira Mani; Rajbhandari Nyachhyon, Armila (Scientific World, 2022)
Zinc oxide (ZnO) nano additives were successfully synthesized in laboratory by precipitation technique. The XRD showed crystalline nature of ZnO with the average crystallite size of 16 nm. The stretching band of ZnO was found at around 400 cm-1 to 600 cm-1 wave number in FTIR. The prepared nano particle have been used as nano additive and sodium lauryl sulphate (SLS) as surfactant, in base oil to improve physio-chemical parameter of lubricants. The result revealed that the additive blended base oil (lubricant) has shown excellent lubrication properties. The higher kinematic viscosity of 90.72 and 10.40 were obtained at 40oC and 100o C respectively. Similarly, viscosity index were found to be 96 which was improved indicating the use of lubricant in slightly high temperature is possible. The pour point was found to be decreased to -9.2oC which was quite significant and could be used in cold environment. The flash point was also found to be increased from 225o C to 230oC which indicated that the prepared nano additive ZnO acts as flash point enhancer. The corrosion test done by copper strip comparative method and was found to be 1b for additive indicating the non-corrosive nature. The absence of moisture and pH around the neutral range 6.65 showed that the additive blended lubricant is not harmful for machinery devices.